Evidence for the prepattern/cooption model of vertebrate jaw evolution - Cerny, Robert; Cattell, Maria; Sauka-Spengler, Tatjana; Bronner-Fraser, Marianne; Yu, Feiqiao; Medeiros, Daniel Meulemans (Proceedings of the National Academy of Sciences of the United States of America, 2010)
The appearance of jaws was a turning point in vertebrate evolution because it allowed primitive vertebrates to capture and process large, motile prey. The vertebrate jaw consists of separate dorsal and ventral skeletal elements connected by a joint. How this structure evolved from the unjointed gill bar of a jawless ancestor is an unresolved question in vertebrate evolution. To understand the developmental bases of this evolutionary transition, we examined the expression of 12 genes involved in vertebrate pharyngeal patterning in the modern jawless fish lamprey. We find nested expression of Dlx genes, as well as combinatorial expression of Msx, Hand and Gsc genes along the dorso-ventral (DV) axis of the lamprey pharynx, indicating gnathostome-type pharyngeal patterning evolved before the appearance of the jaw. In addition, we find that Bapx and Gdf5/6/7, key regulators of joint formation in gnathostomes, are not expressed in the lamprey first arch, whereas Barx, which is absent from the intermediate first arch in gnathostomes, marks this domain in lamprey. Taken together, these data support a new scenario for jaw evolution in which incorporation of Bapx and Gdf5/6/7 into a preexisting DV patterning program drove the evolution of the jaw by altering the identity of intermediate first-arch chondrocytes. We present this "Pre-pattern/Cooption" model as an alternative to current models linking the evolution of the jaw to the de novo appearance of sophisticated pharyngeal DV patterning.
Keywords: transkripční faktory bHLH; rozvržení tělního plánu; vývojová regulace genové exprese; Basic Helix-Loop-Helix Transcription Factors; Gene Expression Regulation, Developmental; molekulární sekvence - údaje; mihule; biologická evoluce; Models, Biological; čelisti; Animals; Vertebrates; Transcription Factors; biologické modely; Biological Evolution; transkripční faktory; zvířata; Body Patterning; Lampreys; Molecular Sequence Data; Homeodomain Proteins; Jaw; obratlovci; homeodoménové proteiny